44. SLEEP QUALITY OF MEDICAL STAFF AND RELATED FACTORS AT THACH THAT DISTRICT GENERAL HOSPITAL, HANOI (Vietnam Journal of Community Medicine, 2025)
Objective: To survey and assess the current state of sleep quality and the factors affecting sleep among healthcare workers at Thach That District General Hospital, Hanoi.Methods: A cross-sectional study was conducted on 200 healthcare workers working at Thach That District General Hospital from March 2024 to August 2024.Results: The rate of insomnia among HCWs in the study was 40.5%, with 29% experiencing mild insomnia, 10% moderate insomnia, and 1.5% severe insomnia. Logistic regression analysis showed that overweight/obese HCWs had a 3.2 times higher risk of insomnia compared to those of normal status. HCWs with less than 30 minutes of physical activity per day had a 2.07 times higher risk of insomnia compared to those with 30 minutes or more, and HCWs with chronic diseases had a 4.04 times higher risk of insomnia compared to those without chronic conditions.Conclusion: Insomnia is prevalent among healthcare workers and is associated with factors such as being overweight, low physical activity, and having chronic diseases.
Keywords: Sleep quality; insomnia; sleep disorders; healthcare workers